High yield purification of full-length functional hERG K+ channels produced in Saccharomyces cerevisiae. Issue 1 (December 2015) - Molbaek, Karen; Scharff-Poulsen, Peter; Helix-Nielsen, Claus; Klaerke, Dan; Pedersen, Per
Abstract The hERG potassium channel is essential for repolarization of the cardiac action potential. Due to this vital function, absence of unintended and potentially life-threatening interactions with hERG is required for approval of new drugs. The structure of hERG is therefore one of the most sought-after. To provide purified hERG for structural studies and new hERG biomimetic platforms for detection of undesirable interactions, we have developed a hERG expression platform generating unprecedented amounts of purified and functional hERG channels. Full-length hERG, with or without a C-terminally fused green fluorescent protein (GFP) His8 -tag was produced from a codon-optimized hERG cDNA inSaccharomyces cerevisiae . Both constructs complemented the high potassium requirement of a knock-outSaccharomyces cerevisiae strain, indicating correct tetramer assemblyin vivo . Functionality was further demonstrated by Astemizole binding to membrane embedded hERG-GFP-His8 with a stoichiometry corresponding to tetramer assembly. The 156 kDa hERG-GFP protein accumulated to a membrane density of 1.6%. Fluorescence size exclusion chromatography of hERG-GFP-His8 solubilized in Fos-Choline-12 supplemented with cholesteryl-hemisuccinate and Astemizole resulted in a monodisperse elution profile demonstrating a high quality of the hERG channels. hERG-GFP-His8 purified by Ni-affinity chromatography maintained the ability to bind Astemizole with the correct stoichiometry indicating that the native, tetrameric structure was preserved. To our knowledge this is the first reported high-yield production and purification of full length, tetrameric and functional hERG. This significant breakthrough will be paramount in obtaining hERG crystal structures, and in establishment of new high-throughput hERG drug safety screening assays.